Synthesis, structures, and reactions of titanium, scandium, and yttrium complexes of diamino-bis(phenolate) ligands: Monomeric, dimeric, neutral, cationic, and multiply bonded derivatives - Boyd, C; Toupance, T; Tyrrell, B; Ward, B; Wilson, C; Cowley, A; Mountford, P (2005)
The synthesis, structures, and selected reactions of new scandium, yttrium, and titanium compounds containing the O 2RNŃ ligands are discussed. The O 2RNŃ ligands can enforce six-coordination, resulting in the formation of dimeric species. The steric protection provided by the phenoxide ring ortho tert-butyl groups of O 2tBuNŃ is anadequate for blocking dimerization through the phenoxy O atoms for larger or more Lewis acidic metal centers. Monoalkyl cations derived from M(O 2RNŃ)-R 2 appear to be dimeric for M = Ti and R = Me.